2022
DOI: 10.1029/2022jc018541
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fronts in Horizontal Transports of the Changjiang River Plume in Summer and the Implications for Phytoplankton Blooms

Abstract: The plume is supercritical upstream of the near-field fronts and subcritical downstream, providing residence time for phytoplankton • The plume currents are in geostrophic balance near the near-field fronts, weakening the cross-shore flows and leading to mass convergence • Transport barriers always exist in the frontal regions either including or excluding tidal influence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 116 publications
0
11
0
Order By: Relevance
“…Additionally, the concentrations of nutrients in the surface water of the central gulf during winter (average of 1.64 ± 1.25 μmol L −1 and 0.52 ± 0.11 μmol L −1 for DIN (dissolved inorganic nitrogen, the sum of NH 4 + , NO 3 − and NO 2 − ) and PO 4 3− , respectively) were remarkably higher than that in summer (average of 0.84 ± 0.46 μmol L −1 and 0.26 ± 0.05 μmol L −1 for DIN and PO 4 3− , respectively), suggesting that the nutrient supply is the key factor for phytoplankton blooms in the central gulf. Because of the convergence effect, nutrients carried by different water masses would converge in the frontal region, thus stimulating phytoplankton growth (Chapman et al., 2020; S. Li et al., 2022; Prants, 2022). In the north, strong frontal intensity and high Chl‐ a concentrations were found during winter (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the concentrations of nutrients in the surface water of the central gulf during winter (average of 1.64 ± 1.25 μmol L −1 and 0.52 ± 0.11 μmol L −1 for DIN (dissolved inorganic nitrogen, the sum of NH 4 + , NO 3 − and NO 2 − ) and PO 4 3− , respectively) were remarkably higher than that in summer (average of 0.84 ± 0.46 μmol L −1 and 0.26 ± 0.05 μmol L −1 for DIN and PO 4 3− , respectively), suggesting that the nutrient supply is the key factor for phytoplankton blooms in the central gulf. Because of the convergence effect, nutrients carried by different water masses would converge in the frontal region, thus stimulating phytoplankton growth (Chapman et al., 2020; S. Li et al., 2022; Prants, 2022). In the north, strong frontal intensity and high Chl‐ a concentrations were found during winter (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, periodic offshore blooms (POB) can be induced by the ocean fronts with seasonal characteristics (Guo et al., 2017; Qi et al., 2022). Since offshore waters are less affected by human activities and nutrient‐rich water masses, almost all previous studies about POBs focused on the role of vertical mixing and the upwelling of deeper nutrients by ocean fronts (Guo et al., 2017; S. Li et al., 2022; Taylor & Ferrari, 2011). For example, a POB was reported in the Luzon Strait, which frequently occurred in the northwest of Luzon Island in winter (Peñaflor et al., 2007; Shang et al., 2012; Tang et al., 1999), and the intensity of the POB is positively correlated with the intensity of the ocean front (Guo et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LCSs were utilized to identify the spatial dynamical structures and to investigate the horizontal transport characteristics in the basin‐slope areas at depth. The LCSs can be quantified by the finite‐size lyapunov exponent (FSLE), which has been used to reveal the horizontal transport and track plankton populations moving with currents (d'Ovidio et al., 2015; Lévy et al., 2018; Li et al., 2022). The FSLE is computed from the time interval τ , at which two fluid particles move from an initial separation of δ i to a final separation distance δ f following their trajectories in the two‐dimensional velocity field.…”
Section: Methodsmentioning
confidence: 99%
“…In summer, a tremendous amount of river discharge leads to a huge plume region off the CE (Hu et al, 1995;Lie et al, 2003). The river plume significantly regulates the hydrodynamics and nutrient conditions off the CE (Mao et al, 1963;Chang and Isobe, 2003;Zhang et al, 2007;Zhu et al, 2009;Li et al, 2022). Cased by abundant nutrient export, severe eutrophication (Chai et al, 2006;Zhu et al, 2014;Wang et al, 2021b) can form off the CE, and the harmful algal blooms (Li et al, 2014;Yu et al, 2018;Wang et al, 2019b) and subsequent bottom hypoxia (Wang et al, 2016;Wei et al, 2017) are frequently observed during the rainy season.…”
Section: Study Areamentioning
confidence: 99%